1990
DOI: 10.1007/bf01815272
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic autonomic neuropathy: Abnormal cardiovascular reactions under general anesthesia

Abstract: The influence of diabetic autonomic neuropathy upon the behavior of the circulatory system was investigated in 56 patients who had undergone ophthalmological surgery. A standardized test combination (variability in heart rate during deep breathing. Valsalva ratio, 30:15 ratio, change in blood pressure from lying to standing, sustained handgrip test) was used to study the patients' cardiovascular reflectory reactions. The patients were then divided into the following groups: Group I, non-diabetics. Group II, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
19
2
1
Order By: Relevance
“…Patients with diabetic autonomic neuropathy and autonomic failure may have increased instability of blood pressure and increased intraoperative mortality. [10][11][12][13] In addition, the function of small myelinated and unmyelinated fibers may improve with treatment. For instance, Fagius et al 14 found improvement in heart rate deep breathing in diabetics treated with aldose reductase inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with diabetic autonomic neuropathy and autonomic failure may have increased instability of blood pressure and increased intraoperative mortality. [10][11][12][13] In addition, the function of small myelinated and unmyelinated fibers may improve with treatment. For instance, Fagius et al 14 found improvement in heart rate deep breathing in diabetics treated with aldose reductase inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6] Diabetes patients with cardiovascular autonomic neuropathy (CAN) are at even greater risk of hypotension during surgery. 4,5,7 Lower body negative pressure (LBNP) is an excellent model for acute haemorrhage and hypovolaemic circulatory stress. 8,9 Orthostatic hypotension is more common in diabetes patients, 3,4 but also diabetes patients with no or only mild neuropathy have increased risk of orthostatic hypotension, signalling other contributory factors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Keyl et al [8] found no relationship between hemodynamic instability during anesthetic induction and abnormal autonomic function tests, although most of the diabetic patients they studied had impaired autonomic function. However, many other reports [2][3][4][5][6][7]9] emphasize the importance of diabetic neuropathy in patients with hemodynamic instability during the perioperative period. Latson et al [7] speculated several probable mechanisms for this hemodynamic instability.…”
Section: Hemodynamic Instabilitymentioning
confidence: 99%
“…There are many reports related to hemodynamic instability during induction and maintenance of anesthesia in diabetic patients [2][3][4][5][6][7]. Burgos et al [2] examined the effects of diabetes on hemodynamic instability in patients undergoing elective ophthalmic surgery under general anesthesia.…”
Section: Hemodynamic Instabilitymentioning
confidence: 99%